Glacial and periglacial data integration in a GIs: methodology used in the Serra da Estrela, Portugal - Vieira, Goncalo (2019)
The methodology applied in the research in Serra da Estrela (Portugal) is to integrate glacial and periglacial geomorphological data in a Geographical Information System and a Database Management System. The main objective of the procedure is to make use of low cost software for geospatial data integration, statistical analysis and production of geomorphological mag. The digital storage format provides the means for fast access and easy transportation of the data during field campaigns. It is also a very useful way to store the geomorphological data, so it can be used in the future by other researchers working in the area.